Importancia de la determinación de microalbuminuria como ayuda de diagnóstico de nefropatías diabéticas en pacientes diabéticos atendidos en el hospital provincial general docente de riobamba durante el período de febrero a julio del 2011 - Miranda Tenesaca, Erica Paulina (2012)
This work contains basic knowledge about the importance of technology to help diagnose microalbuminuria diabetic nephropathy in diabetic patients Club General Teaching Hospital in Riobamba, considered as a disease that occurs in people with diabetes when their control of glucose in blood and other associated factors require immediate attention This research consists of general and specific objectives that are related to the topic, is justified by having a broad understanding of the causes and consequences that can occur at the time not to treat this disease